Failed transarterial embolization of subserosal uterine arteriovenous malformation - Seo, Kyung Jin (Korean Society of Obstetrics and Gynecology; Korean Society of Contraception and Reproductive Health; Korean Society of Gynecologic Endocrinology; Korean Society of Gynecologic Endoscopy and Minimal Invasive Surgery; Korean Society of Maternal Fetal Medicine; Korean Society of Ultrasound in Obstetrics and Gynecology, 2013)
Uterine arteriovenous malformation (AVM) is rare but potentially life-threatening from excessive vaginal bleeding. All uterine AVMs reported to date have been found in the endometrial or myometrial layers. Here we present a patient with a subserosal type AVM on the fundus of uterus, which spontaneously ruptured.